Um estudo sobre manifestações antidemocráticas no Recife (2013-2016): entre as “jornadas de junho” e o impeachment de Dilma Rousseff. - Grangeiro, Giovanna de Lima (2023)
This research aims to answer how the media in Pernambuco dealt with the historical fact of the Impeachment of former president Dilma Rousseff, contextualizing the demonstrations that took place from June 2013 until the coup in August 2016, in which the adhesion of extremist groups was noted, who mobilized in actions that aimed to undermine Human Rights, the Institutions of the Republic, Democracy and the Rule of Law. The aim of the work is to understand how major newspapers in circulation in the city of Recife, such as Diário de Pernambuco, Folha de Pernambuco and Jornal do Commercio, conveyed this news to society, with a detailed analysis of the day following the coup, that is, analysis of newspapers from 09/01/2016. Through research, using the method of content analysis and discourse analysis. The theoretical foundation was supported by the studies of Tânia Regina de Luca, which served as a reference on how to deal with journalistic sources, as well as the teachings of Hannah Arendt, Daniel Ziblatt, Steven Levitsky, Maria da Gloria Gohn, Rosana Pinheiro, José M. de Carvalho, and those of F. Dosse for the analysis of contemporary time. As a proposal to contribute to the study of History and as an alert to the importance of defending democracy, a booklet on the topic was created, especially for high school students.